Mobile Positioning Data: Prediktor Produk Domestik Regional Bruto (PDRB) Pada Masa Pandemi - Amanda Pratama Putra; Heny Wulandari (Seminar Nasional Official Statistics, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic has devastated economic activity in many countries, including Indonesia. Big data as an alternative data source to measure economic activity, especially in a pandemic situation, can be a valuable mine of information. In the present research, a new approach for measuring economic activities based on mobile positioning data (MPD) has been developed. The sample dataset of mobile network subscribers’ activity was aggregated at the area municipality level by the daily interval, where the activity itself is defined as the number of mobile transactions and detected locations, and the number of unique users. This paper shows that mobile positioning data (MPD) can be a proxy to estimate economic activity in Indonesia, especially during pandemic conditions.